Biological Functions and Regulatory Mechanisms of Hypoxia-Inducible Factor-1α in Ischemic Stroke - He, Qianyan; Ma, Yinzhong; Liu, Jie; Zhang, Dianhui; Ren, Jiaxin; Zhao, Ruoyu; Chang, JunLei; Guo, Zhen-Ni; Yang, Yi (Frontiers in Immunology, 2021)
Ischemic stroke is caused by insufficient cerebrovascular blood and oxygen supply. It is a major contributor to death or disability worldwide and has become a heavy societal and clinical burden. To date, effective treatments for ischemic stroke are limited, and innovative therapeutic methods are urgently needed. Hypoxia inducible factor-1α (HIF-1α) is a sensitive regulator of oxygen homeostasis, and its expression is rapidly induced after hypoxia/ischemia. It plays an extensive role in the pathophysiology of stroke, including neuronal survival, neuroinflammation, angiogenesis, glucose metabolism, and blood brain barrier regulation. In addition, the spatiotemporal expression profile of HIF-1α in the brain shifts with the progression of ischemic stroke; this has led to contradictory findings regarding its function in previous studies. Therefore, unveiling the Janus face of HIF-1α and its target genes in different type of cells and exploring the role of HIF-1α in inflammatory responses after ischemia is of great importance for revealing the pathogenesis and identifying new therapeutic targets for ischemic stroke. Herein, we provide a succinct overview of the current approaches targeting HIF-1α and summarize novel findings concerning HIF-1α regulation in different types of cells within neurovascular units, including neurons, endothelial cells, astrocytes, and microglia, during the different stages of ischemic stroke. The current representative translational approaches focused on neuroprotection by targeting HIF-1α are also discussed.